Functional and Visionary Leadership in Self-Managing Virtual Teams - Eseryel, U. Yeliz; Kevin Crowston; Heckman, Robert (Group & Organization Management, 2021)
In this conceptual article, we present a theory of leadership in self-managing virtual teams. We describe leadership in this setting as a process that results in the creation, reinforcement and evolution of shared mental models and shared norms that influence team member behaviour towards the successful accomplishment of shared goals. We distinguish two types of leadership. We identify leadership that works within and reinforces existing models and norms to influence team contributions as “functional” leadership. We identify leadership that results in changes in models and norms as “visionary” leadership. We propose that successful self-managing virtual teams require both types of leadership and that they will exhibit a paradoxical combination of shared, distributed functional leadership complemented by strong, concentrated and centralized visionary leadership and that visionary leadership is enabled by functional leadership in the form of substantive team member contributions.
Keywords: functional leadership; Leadership; Self-managing teams; structuration theory; virtual teams; visionary leadership